2013
DOI: 10.1098/rspb.2013.2330
|View full text |Cite
|
Sign up to set email alerts
|

When to approach novel prey cues? Social learning strategies in frog-eating bats

Abstract: Animals can use different sources of information when making decisions. Foraging animals often have access to both self-acquired and socially acquired information about prey. The fringe-lipped bat, Trachops cirrhosus, hunts frogs by approaching the calls that frogs produce to attract mates. We examined how the reliability of self-acquired prey cues affects social learning of novel prey cues. We trained bats to associate an artificial acoustic cue (mobile phone ringtone) with food rewards. Bats were assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 40 publications
1
51
0
Order By: Relevance
“…Thus, being trained in the presence of a bat that reliably went to B encouraged the observers in group 50-social to reverse their original preference for A over B. According to Jones et al [8], this reversal was a consequence of group 50-social adopting the strategy of copy when dissatisfied, where the dissatisfaction arose from the introduction of the 50% schedule associated with A. Support for this interpretation is provided by the additional finding that during the test, group 100-social, which presumably did not experience dissatisfaction, did not relinquish its original preference for A.…”
Section: Copy When Alternative Unsuccessfulmentioning
confidence: 99%
“…Thus, being trained in the presence of a bat that reliably went to B encouraged the observers in group 50-social to reverse their original preference for A over B. According to Jones et al [8], this reversal was a consequence of group 50-social adopting the strategy of copy when dissatisfied, where the dissatisfaction arose from the introduction of the 50% schedule associated with A. Support for this interpretation is provided by the additional finding that during the test, group 100-social, which presumably did not experience dissatisfaction, did not relinquish its original preference for A.…”
Section: Copy When Alternative Unsuccessfulmentioning
confidence: 99%
“…As cooperation both between related and unrelated females is frequently observed in this species (Carter & Wilkinson, ), (kin)cooperation seems to be the driving force for the observed female philopatry and male‐biased dispersal. While T. cirrhosus can quickly acquire novel foraging behavior by observing conspecifics (Jones, Ryan, Flores, & Page, ; Page & Ryan, ), the social learning observed in this species is via eavesdropping where one individual opportunistically observes the foraging behavior of another. Thus, unlike Desmodus rotundus , female T. cirrhosus are likely not cooperating while foraging or in sharing food resources at the roost.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely both mechanisms contribute to this preference, although we believe that learning might play a greater role than innate preferences as both T. cirrhosus and other bat species have been shown to be highly plastic and quick to learn in their foraging decisions and response to prey cues (Siemers 2001;Page and Ryan 2005;Ratcliffe and ter Hofstede 2005;Jones et al 2013b;O'Mara et al 2014). For example, a reversal learning experiment with T. cirrhosus demonstrated that after only five rewarded trials bats can develop positive phonotaxis toward the call of a poisonous toad species to which they were initially strongly averse (Page and Ryan 2005), and bats can socially learn to associate completely synthetic calls (phone ringtones) as prey calls (Jones et al 2013b). This novel response could then be transmitted rapidly between bats via social learning, suggesting that once an innovative response to prey cue arises, it can spread rapidly in a population (Page and Ryan 2006;Jones et al 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a reversal learning experiment with T. cirrhosus demonstrated that after only five rewarded trials bats can develop positive phonotaxis toward the call of a poisonous toad species to which they were initially strongly averse (Page and Ryan 2005), and bats can socially learn to associate completely synthetic calls (phone ringtones) as prey calls (Jones et al 2013b). This novel response could then be transmitted rapidly between bats via social learning, suggesting that once an innovative response to prey cue arises, it can spread rapidly in a population (Page and Ryan 2006;Jones et al 2013b). An interesting experiment that would serve to elucidate the role of learning in this eavesdropper preference would be to compare the strength of this preference between juvenile bats and adult bats at sites where T. cirrhosus shows a preference for complex calls over simple calls.…”
Section: Discussionmentioning
confidence: 99%